Prepare : Student's book - Kosta, Joanna (Cambridge University Press, 2015)
The Level 3 2nd Edition book features engaging topics, in-depth preparation for the revised 2020 A2 Key for School exam. Students will learn interactive, personalized lessons with topics and resources tailored to their interests. Teachers can take comfort in knowing that each lesson is helping students achieve exam success, and that the course is creating confident English users with an enhanced grammar and vocabulary curriculum. Student Books and Online Workbooks are also available, separately.